2010
DOI: 10.1097/fjc.0b013e3181e23e2b
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Hypertension With a New Adenosine Triphosphate–sensitive Potassium Channel Opener Iptakalim

Abstract: Hypertension is the most common cardiovascular disease. The discovery of the antihypertensive action of adenosine triphosphate-sensitive potassium (K(ATP)) channel openers was a significant advance in the treatment of hypertension. Iptakalim is a novel K(ATP) channel opener with a unique chemical structure that differs from other K(ATP) openers. Among the 3 different subtypes of K(ATP) channels heterologously expressed in human embryonic kidney cells and Xenopus oocytes, iptakalim exhibits significant selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 36 publications
1
36
0
1
Order By: Relevance
“…In aortic endothelial cells, K ATP channels consist of a heteromultimeric complex of Kir6.1, Kir6.2, and SUR2B subunits [19] . Glibenclamide and iptakalim bind with different sites on the regulatory subunit, the sulfonylurea receptor [20] . However, some investigators reported that chemerin expression and secretion were enhanced in lupus erythematosus dermal endothelial cells and in interleukin-1β-stimulated adipocytes [13,21] .…”
Section: Discussionmentioning
confidence: 99%
“…In aortic endothelial cells, K ATP channels consist of a heteromultimeric complex of Kir6.1, Kir6.2, and SUR2B subunits [19] . Glibenclamide and iptakalim bind with different sites on the regulatory subunit, the sulfonylurea receptor [20] . However, some investigators reported that chemerin expression and secretion were enhanced in lupus erythematosus dermal endothelial cells and in interleukin-1β-stimulated adipocytes [13,21] .…”
Section: Discussionmentioning
confidence: 99%
“…KCNJ11 E23K polymorphisms may also affect therapeutic efficacy of repaglinide [26,27] . Iptakalim exhibits mild effects on SUR2A/Kir6.2 channels [8] . It is possible that the different composition of Kir6.2 pore-forming proteins might in part account for the different SBP response to iptakalim in Chinese Han hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 3 different subtypes of K ATP channels heterologously expressed in human embryonic kidney cells and Xenopus oocytes, iptakalim exhibits significant selectivity for SUR2B/Kir6.1 channels, mild effects on SUR2A/ Kir6. 2 [8] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abundant previous pharmacological studies have demonstrated that iptakalim is a highly selective K ATP channel opener, which can preferentially relax small arteries and effectively reduce blood pressure [10,11] . Another article published in Acta Pharmacologica Sinica suggested that iptakalim, via activating K ATP channels, enhances the endothelial chemerin/ChemR23 axis and NO production and thus improves endothelial function [12] .…”
mentioning
confidence: 99%